DETERMINAN TUNNELLING INCENTIVE PADA PERUSAHAAN SEKTOR ENERGI DI INDONESIA - Rahel Junita (UNIVERSITAS DHARMAWANGSA, 2026)
Tunneling incentive remains a critical issue in corporate governance, particularly in energy sector companies characterized by concentrated ownership structures and high related-party transactions. The purpose of this study is to investigate the impact of transfer pricing, debt covenant, and profitability on tunneling incentives in energy businesses listed on the Indonesia Stock Exchange between 2021 and 2025. Partial Least Square (PLS) analysis utilizing SmartPLS 4 is used in this quantitative study. Purposive sampling is used to choose samples from financial statements and annual reports that contain secondary data. The findings reveal that profitability does not have a significant effect on tunneling incentive, indicating that higher earnings do not necessarily lead to opportunistic behavior by controlling shareholders. In contrast, transfer pricing shows a positive and significant effect, suggesting that related-party transactions are commonly used as a mechanism for resource shifting. Meanwhile, debt covenant has a significant negative effect, implying that stricter creditor monitoring reduces the likelihood of tunneling practices. Furthermore, the variables simultaneously have a significant effect on tunneling incentive, with an R-Square value of 0.780, indicating strong explanatory power. These results highlight that tunneling incentive practices are more influenced by transaction structures and external monitoring mechanisms rather than profitability levels, emphasizing the importance of governance and regulatory oversight in the energy sector